1999
DOI: 10.1111/j.2042-3306.1999.tb05275.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fibre on hydration status after dehydration with frusemide

Abstract: Summary Three diets were fed to 6 horses in a 3 × 6 Latin rectangle experiment to determine if dietary fibre could improve hydration status in response to dehydration with frusemide. Frusemide was used to simulate dehydration from exercise‐induced sweat loss. Diets contained similar dry matter (DM), energy, protein and electrolyte content, but differed in total dietary fibre (TDF) and/or soluble fibre (SDF). The 3 diets were: 1) HIGH‐HIGH (high TDF, high SDF); 2) HIGH‐LOW (high TDF, low SDF); and 3) LOW‐LOW (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The horses drank more water when fed the hay-only diet (HAY) compared with the concentrate diets (BAR + SBP and BAR) in agreement with previous studies where forage-only diets have been compared with mixed rations (Fonnesbeck, 1968;Warren et al, 1999). It has been suggested that the hindgut can act as a fluid reservoir when fibre-based diets are fed (Meyer, 1987), but also that fibre composition might affect water binding and reduce its availability (Cuddeford et al, 1992).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The horses drank more water when fed the hay-only diet (HAY) compared with the concentrate diets (BAR + SBP and BAR) in agreement with previous studies where forage-only diets have been compared with mixed rations (Fonnesbeck, 1968;Warren et al, 1999). It has been suggested that the hindgut can act as a fluid reservoir when fibre-based diets are fed (Meyer, 1987), but also that fibre composition might affect water binding and reduce its availability (Cuddeford et al, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…SBP has been proposed to have other beneficial effects than being a highly fermentable fibre source: for example, improving the water balance in horses (Warren et al, 1999) and having a positive effect on the apparent digestibility of the cell wall fraction when lucerne hay or silage were partly substituted with SBP (Murray et al, 2008). Furthermore, when SBP was included in a diet with barley, caecal pH did not decrease as much after feeding as when the same amount of barley was fed alone (Brøkner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The low Cu and Zn (critical for the bone structure) intakes need to be compensated, too, with supplementation to ensure healthy bone formation [37,39]. The K content was typically high in forages [35], and can negatively affect anion-cation and fluid balances in the horses [57].…”
Section: Nutrient Intakes and Animal Wellbeingmentioning
confidence: 99%
“…Water intake is related to roughage intake. Reducing dietary roughage intake results in decreased water intake [17,18]. Second, rapid consumption of pasture occurring when grazing resumes following a period of grazing restriction could alter fluid balance by way of increased alimentary secretions associated with increased feed intake.…”
Section: Discussionmentioning
confidence: 98%
“…However, the lack of difference in fecal DM would suggest that if there was a change in fluid balance, then it did not chronically impact the hindgut fluid balance. Fecal moisture is influenced by the amount and type of dietary fiber [17]. This is important because large fluctuations in hindgut fluid balance can contribute to impaction colic [4].…”
Section: Discussionmentioning
confidence: 99%